Classifying Object Size in an Arduino-Based RADAR System Using an IR Sensor and I2C-LCD - Uddin, Mohammad Iftekher; Barua, Robin (Journal of Energy and Electrical Engineering, 2025)
The radio detection and ranging (RADAR) system uses electromagnetic waves to measure the distance and direction of an object. The IR (infrared) sensor uses infrared light to detect an object. This study uses the IR sensor to classify the size of an object in an Arduino-based RADAR system. A binary logical method classifies the size of an object as either long or small. The result is displayed on a liquid crystal display (LCD). An I2C module is used to easily connect the LCD to the Arduino. The system has been simulated in Proteus software to verify the Arduino code. The Arduino-based RADAR system with size classification has been implemented using two IR sensors, an ultrasonic sensor, an LCD, and a servo motor. Two IR sensors have been used at different heights to classify the size of an object. A Java application is used to visualize the RADAR system on a PC in a graphical user interface (GUI), which shows the moving object in real-time. The ultrasonic range is programmed at 40 cm to detect objects. The system can detect objects in the 40 cm range and between 0 and 180° angles.